Effects of physical exercise in reducing caregivers burden: a systematic review - Carla Cardoso; Maria José Lumini; Maria José Lumini; Teresa Martins; Teresa Martins (Frontiers in Public Health)
Background and aimCaring for someone can be physically and psychologically demanding, predisposing caregivers to muscle injuries, fatigue, exhaustion, depression, anxiety, and burnout. The literature suggests several approaches to reducing caregiver burden, one of which is physical exercise. The aim of this systematic review was to analyze the effectiveness of exercise-based programs or muscle relaxation in reducing caregiver burden and stress among family caregivers.MethodA systematic literature review was conducted following the PRISMA guidelines. The search was performed in the Web of Science, Cochrane Library and Scopus databases and through the EBSCOhost aggregator (CINAHL Plus, MEDLINE, and SportDiscus). Studies were selected based on the PICOD acronym.ResultsEleven randomized controlled trials (RCTs) and two other experimental studies were included. The reviewed programs encompassed aerobics, strengthening, and muscle relaxation exercises, delivered by various professionals in diverse settings, such as caregivers' homes, gyms, and hospital environments. Although the programs varied in type, duration, and structure, the majority of the studies demonstrated positive effects on caregivers' physical and psychological well-being, along with reductions in burden and stress.ConclusionThe results suggest that physical exercise interventions are effective in reducing caregiver burden and stress, while also enhancing overall well-being. Future strategies should emphasize the importance of raising awareness among caregivers about adopting healthy lifestyles, with a particular focus on regular physical activity, as a means of relaxation and self-care. To maximize the effectiveness of these interventions, incorporating flexible, home-based components and engaging multidisciplinary teams could enhance accessibility, adherence, and impact.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023446129, PROSPERO 2023 CRD42023446129.